Activating Methods and Factors Influencing the Choice Of Fields Studying the Accounting Profession - Izabela EMERLING; Sylwia KRAJEWSKA; Katarzyna CHŁAPEK (Communications of International Proceedings, 2023)
The profession of accountant is an indispensable profession for the proper functioning of any enterprise in a market economy. The accounting profession is constantly evolving, therefore the article fills the existing research gap in this field and is a contribution to further research in this field of knowledge. The aim of the article was to present the importance of activating methods in didactics of universities educating accountants and factors influencing the choice of fields of study in the accounting profession. The applied research methods are based on the study of literature in the studied field and the presentation of the analysis of the choice of directions by students on the basis of surveys. In order to learn more about the main reasons that guide students when choosing a major, a survey was conducted among undergraduate students at three well-known universities. The survey covered 1,000 respondents between 2022 and 2023. The study is in line with the authors' scientific interests in the methodology of education at the university and the importance of methods activating financial and accounting services in contemporary academic education. The conducted research has shown that more and more emphasis is placed on the soft skills of accounting staff, on the ability to solve more and more frequent and difficult problems. Future accountants cannot rely only on theoretical knowledge and knowledge of legal acts in the field of accounting, their role will not consist in entering accounting documents, but in their in-depth analysis. Therefore, it is expected that in addition to knowledge of current tax regulations, an accountant must have highly developed analytical skills and be creative, which will allow combining Knowledge from various fields in order to make the most effective management decisions.
Keywords: Didactics; Activating Methods; Accounting Profession; Skills